Pengaruh motivasi belajar dan kepercayaan diri terhadap kemampuan berpikir kritis mahasiswa Pendidikan Ekonomi Universitas Negeri Medan - Muhammad Bukhori Dalimunthe; Deni Adriani; Silvia Annur Hasibuan; Monika Flora Manik; Rini Khairani Harahap; Amelia Amelia (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study is motivated by the persistently low level of students’ critical thinking skills, reflected in passive information acceptance, superficial analysis, and limited willingness to express opinions during learning. These issues are presumed to be associated with suboptimal learning motivation and self-confidence. This research aims to examine the effect of learning motivation and self-confidence on the critical thinking skills of Economics Education students at Universitas Negeri Medan. A quantitative approach was employed using multiple linear regression analysis with SPSS. Data were collected through questionnaires from students selected via simple random sampling. The findings indicate that both learning motivation and self-confidence have a positive and significant effect on critical thinking skills, both individually and simultaneously. This suggests that students’ critical thinking ability is shaped by the combined influence of these two factors. Therefore, fostering a learning environment that enhances motivation and builds self-confidence is essential to optimize students’ critical thinking development.